Analysis of Islamization in Syed Muhammad Naquib Al-Attas' Thoughts on the Childfree Phenomenon - Musyarrofah, Musyarrofah; Achmad Khudori Soleh; M. Aunul Hakim (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2026)
The childfree phenomenon, as a conscious decision not to have children, is becoming increasingly prominent in modern society and sparking debate, particularly when linked to family values ​​and religious perspectives. This study aims to analyze the childfree phenomenon through the framework of Syed Muhammad Naquib Al-Attas's Islamization of knowledge, by tracing the elements of the secular worldview that underpin key concepts such as freedom, humanity, nature, and marriage. This research uses a qualitative method with a literature study approach, as well as a conceptual analysis of Al-Attas's thinking and contemporary childfree discourse. The research findings indicate that (1) the childfree phenomenon is not neutral, but rather rooted in a modern, secular worldview that separates freedom from moral and transcendent dimensions and views the relationship between humans and nature instrumentally. (2) From Al-Attas's perspective on Islamization, the main problem with being childfree lies in conceptual errors resulting from the loss of adab, not solely in individual choice. (3) Therefore, Islamization is directed toward restoring the meaning of key concepts based on monotheism, human nature, and etiquette, so that freedom, marriage, and human relations with nature are understood anew within the framework of responsibility and the purpose of human creation as servants and vicegerents.